Experimental design and optimization of a novel solids feeder device in energy efficient pneumatic conveying systems - Adriano Gomes de Freitas; Ricardo Borges dos Santos; Luis Alberto Martinez Riascos; Jose Eduardo Munive-Hernandez; Shibo Kuang; Ruiping Zou; Aibing Yu (Energy Reports, 2023)
Pneumatic conveying of powders is an engineering process used for conveying dry granulate or powder material where energy consumption is a significant cost factor and contributes to greenhouse gas emissions. In this RD&I project, work was conducted to model pneumatic conveying and bulk characteristics of the particulate product being conveyed. Because pneumatic conveyance is highly empirical, general models are difficult to establish. Due to these limitations, evaluating energy efficiency is usually limited to a specific experimental range of conditions. This work is based on engineering optimization of a workflow with data from an industrial operation commanded by a Programmable Logic Controller (PLC) with a control algorithm, performing logical, sequential, and timed tasks for plant control. The PLC communicates with a Human–Machine Interface and a Supervision and Control System, which are the means of interaction through a graphical environment interface with the process operator. By applying mathematics to introduce a systematic method to select the gas (air) pressure and flow necessary to operate a pneumatic conveying system in dense phase mode, it has been shown, on an industrial scale of 10 t/h, the feasibility of controlling an efficient pneumatic conveying system manipulating only two input parameters. This allows operation at pre-determined conveying rates with lower operational expenditures. The same methodology can be explored for several other systems.